2013
DOI: 10.7897/2230-8407.041106
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Uv Spectrophotometric Method for Determination of Ceftazidime in Bulk and Pharmaceutical Formulation

Abstract: The present study was undertaken to develop and validate a simple, accurate, precise, reproducible and cost effective UV-Visible spectrophotometric method for the estimation of ceftazidime in bulk and pharmaceutical formulation. The solvent used throughout the experiment was the mixer of methanol and water. Absorption maximum (λmax) of the drug was found to be 266 nm. The quantitative determination of the drug was carried out at 266 nm and Beer's law was obeyed in the range of 2-20 μg/mL. The method was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…1 The literature review revealed that several analytical approaches have been utilised in the determination of cefotaxime such as HPLC, UV-VIS spectrophotometric, potientiometry, electrophoresis and hydrophilic interaction chromatography. [2][3][4][5][6][7][8][9] Paracetamol (PAR); N-(4-Hydroxyphenyl) acetamide (Fig. 1) is related to a non-steroidal anti-inflammatory drugs (NSAIDs) which acts centrally and peripherally for treatment of non-inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 The literature review revealed that several analytical approaches have been utilised in the determination of cefotaxime such as HPLC, UV-VIS spectrophotometric, potientiometry, electrophoresis and hydrophilic interaction chromatography. [2][3][4][5][6][7][8][9] Paracetamol (PAR); N-(4-Hydroxyphenyl) acetamide (Fig. 1) is related to a non-steroidal anti-inflammatory drugs (NSAIDs) which acts centrally and peripherally for treatment of non-inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this difficulty, Babitan et al as well as Umme Bushra et al have each developed and validated a method for analyzing Cefixim using a non-separating technique which is Ultraviolet-visible spectrophotometry using methanol as a solvent [4]. A part from these previous researches, another Spectrometric Method using Methanol and water as solvent was developed, to deal with analysis of Cefixim in 287 nm as maximal wavelength to the measurement [5]. The method is simple and less expensive than Liquid Chromatography but requires the use of organic solvent which costs more.…”
Section: Introductionmentioning
confidence: 99%